Trust Buffers Against Reduced Life Satisfaction When Faced With Financial Crisis - Clench-Aas, Jocelyne; Bergande, Ingrid; Nes, Ragnhild Bang; Holte, Arne (Frontiers in Psychology, 2021)
Background: In light of the covid-19 pandemic, and its large economic consequences, we used a three-layer nested structural model (individual, community, country), each with a corresponding measure of income, trust and satisfaction, to assess change in their interrelationships following global crisis; here, the financial crisis 2008/2009. Methods: With multilevel techniques, we analyzed data from two waves (2006, 2012) of the European Social Survey in 19 countries (weighted N = 73,636) grouped according to their levels of trust. Results: In high trust countries, personal life satisfaction (LS) was not related to personal, community, or national income before or after the crisis. By contrast, in low trust countries, LS was strongly related to all three forms of income, especially after the crisis. In all country groups, personal, social, and political trust moderated their respective effects of income on LS (“The buffer hypothesis”). Political trust moderated the effects of income more strongly in low trust countries. The moderating effect of political trust increased sharply after the crisis. After the crisis, national level factors (e.g. political trust, national income) increased their importance for LS more than factors at the local and individual level. However, the relative importance of all three forms of income to LS increased after the crisis, to the detriment of trust. Conclusion: Economic crises seem to influence personal LS less in high trust countries compared to low trust countries. Hence, high trust on a national level appears to buffer the negative impact of a financial crisis on personal satisfaction. Overall, factors at the national level increased their impact during the financial crisis. When facing a global crisis, actions taken by institutions at the country level may thus become even more important than before the crisis.